Regional convergence in Germany: A geographically weighted regression approach - Hans-Friedrich Eckey; Reinhold Kosfeld; Matthias Türck (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2005)
The convergence of German regions represents a politically explosive question. Different studies examined convergence processes of Germany. We derive equations to estimate the convergence speed on basis of a Solow model, to which human capital is added. The geographically weighted regression permits a detailed analysis of convergence processes, which has not been conducted for Germany so far yet. We estimate a separate speed of convergence for every region, which results from the local coefficients of the regression equations. The application of this procedure to German labour market regions shows that regions move with a different speed towards their steady state level. The half lives are substantially longer in the manufacturing sector than in the service sector. One model even yields tendencies towards divergence of some peripheral regions.
Keywords: C21; R11; R58; 330; Regional Convergence; Spatial Econometrics; Geographically Weighted Regression; Entwicklungskonvergenz; Regionaler Arbeitsmarkt; Regression; Deutschland